TINJAUAN LITERATUR SISTEMATIS: PERAN INOVASI SEBAGAI VARIABEL MEDIASI DAN MODERASI TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH - M. Hamsal; Arta M. Sundjaja; Willy Gunadi; Nasir, Munawir (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Systematic literature review focusing on innovation variables as moderating and mediating exogenous variables on MSMEs performance is relatively rare. This study aimed to determine factors affecting MSMEs performance mediated or moderated by innovation variables. The article search used the Google Scholar database. Of 500 articles, 320 were excluded based on title and abstract and 180 were screened for eligibility, resulting in 35 articles for review. The study found that innovation mediated 30 exogenous variables on MSMEs performance. There were 15 innovation variables; Innovation and Innovation Capability were the most used by researchers. Additionally, innovation variables such as Product Innovation, Innovation Culture, Innovation, Process Innovation, and Innovation Capability moderated about six exogenous variables on MSMEs performance. Innovation research with moderating models was still relatively small compared to mediation models.